1996
DOI: 10.1159/000134495
|View full text |Cite
|
Sign up to set email alerts
|

A novel multicolor hybridization scheme applied to localization of a transcribed sequence (D10S170/H4) and deletion mapping in the thyroid cancer cell line TPC-1

Abstract: The sequence-tagged site (STS) D10S170, also referred to as H4, is a gene of unknown function. Its 5’ end was found fused to the catalytic domain of the RET protooncogene to generate RET/PTC1, the most common form of PTC onco-genes in human papillary thyroid carcinoma. This gene has previously been assigned to a very large genomic region, 10q11.22→q22.1. Here, we describe the application of a novel hybridization scheme to the physical and genetic mapping of D10S170. First, we selected a homologous large-insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 5 publications
0
33
0
Order By: Relevance
“…A group of pathologists have reported that 90% of RET/PTC1 positive thyroid tumours fail to express the unrearranged allele of H4(D10S170) (Sheils et al, 2000). The same phenomenon has been observed in the TPC-1 thyroid papillary carcinoma cell line, a line harbouring RET/PTC1 oncogene activation that has been reported to have a gene deletion encompassing the normal H4(D10S170) allele (Jossart et al, 1996). Taken together, these data suggest that the presence of the unrearranged normal H4(D10S170) gene product could exert a negative action on cell proliferation and that a growth advantage might result from the loss of the normal allele of this gene, likely during tumour progression.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A group of pathologists have reported that 90% of RET/PTC1 positive thyroid tumours fail to express the unrearranged allele of H4(D10S170) (Sheils et al, 2000). The same phenomenon has been observed in the TPC-1 thyroid papillary carcinoma cell line, a line harbouring RET/PTC1 oncogene activation that has been reported to have a gene deletion encompassing the normal H4(D10S170) allele (Jossart et al, 1996). Taken together, these data suggest that the presence of the unrearranged normal H4(D10S170) gene product could exert a negative action on cell proliferation and that a growth advantage might result from the loss of the normal allele of this gene, likely during tumour progression.…”
Section: Discussionmentioning
confidence: 71%
“…The same results ( Figure 2a) were obtained in a human thyroid papillary carcinoma cell line, established from a tumour carrying the RET/PTC1 oncogene activation, named TPC-1. It has been shown that these cells have lost by deletion the wt H4(D10S170) allele not involved in the rearrangement with RET (Jossart et al, 1996).…”
Section: H4 Is a Nuclear And Cytosolic Proteinmentioning
confidence: 99%
“…Transient expression of H4(D10S170) gene product was associated with induction of apoptosis in thyroid cells. TPC-1 cells, which harbours the RET/PTC1 rearrangement and have lost the expression of the normal unrearranged H4(D10S170) allele (Jossart et al, 1996), transiently transfected with H4(D10S170)wt, showed impaired apoptosis if pretreated with 50 nM wortmannin, 1 mM caffeine and 10 mM KU55933 (Hickson et al, 2004), known inhibitors of ATM kinase activity (Figure 5a). In addition, in TPC-1 cells, H4 T434A expression had a dominant negative effect on H4wt-mediated apoptosis (Figure 5a).…”
Section: H4(d10s170) Location and Phosphorylation In A-t Cellsmentioning
confidence: 99%
“…The order of these probes on 10q is reported elsewhere. 32 The RET probe was labeled with SpectrumGreen™-dUTP and the H4 probe with SpectrumRed™-dUTP (Vysis, Inc., Richmond, UK) using the Nick Translation Kit (Vysis, Inc.). A standard hybridization method was used according to the manufacturer's protocol.…”
Section: Fluorescence In Situ Hybridization (Fish) Analysismentioning
confidence: 99%
“…This suggests that H4 may be a tumor suppressor gene. 32 We evaluated H4 gene expression in FB-2 cells by using a semiquantitative RT-PCR and primers encompassing the 3Ј half of the gene downstream from the rearrangement. Like TPC-1 cells, FB-2 cells did not express the H4 gene (Fig.…”
Section: Ret Rearrangement In Fb-2 Cellsmentioning
confidence: 99%